EDUKASI PEMORSIAN PIRING MAKAN UNTUK PENCEGAHAN OBESITAS PADA WANITA USIA SUBUR DI WILAYAH KERJA UPTD (Unit Pelaksana Teknis Dinas) PUSKESMAS CISALAK PASAR - Nuchar, Regina Ekidika; ilmi, ibnu malkan bakhrul; Wibowo, Aprilian Tri Wibowo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2023)
Nutritional problems that occur in reproductive-age women consist of anemia, chronic energy deficiency,hypertension and obesity. Obesity is a major problem with a prevalence in the city of Depok of 35.69% in womenaged over 18 years. Reproductive-age women who are obese can cause hypertension, diabetes mellitus, and if thisoccurs during pregnancy it can have a negative impact on the pregnancy. Obesity is the accumulation of fat thatoccurs due to an imbalance between energy intake and energy used over a long period of time. One way to reduceweight in obese people is to control food intake according to recommendations. Recommended food portions areregulated in balanced nutrition guidelines. The form of application of balanced nutrition guidelines is to make aportioning plate called